Antecedents and Consequences of Hedonic Satisfaction and Eudaimonic Satisfaction of Visitors to the Cianjur Regional Library - Nisrina Hanifa Azmi; Yadi Ernawadi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to predict the dimensions of LibQUAL (library personnel, library resources and user services, and facilities and equipment) and self-service behavior as predictors of revisit intention through hedonic satisfaction and eudaimonic satisfaction of visitors to the Cianjur Regional Library. Expectation confirmation theory (ECT) is the basis for developing a conceptual model. This study uses a quantitative approach through a survey method with data collection in the form of questionnaires to 153 library visitors. Data were analyzed using structural equation modeling (SEM) techniques to analyze data with the help of the SmartPLS version 3.0 tool.The results of the study indicate that library personnel, library resources and user services, and facilities and equipment have a positive influence on revisit intention, both directly and indirectly through hedonic satisfaction. Furthermore, self-service behavior has the strongest influence on revisit intention, both directly and indirectly through eudaimonic satisfaction. The findings of this study are expected to contribute to future research and the management of the Cianjur Regional Library in designing strategies that can increase revisit intention. Further research is recommended to consider exploring other predictors of revisit intention.